2012
DOI: 10.1111/j.1474-919x.2012.01240.x
|View full text |Cite
|
Sign up to set email alerts
|

Consistent contrast between eyelid and iris brightness supports a role for vigilance signalling in ducks

Abstract: Signalling self‐ability to maintain vigilance may help in securing a mate, while providing accurate information about vigilance status may result in conspecifics adjusting their own scanning rate of the environment, potentially to the individual's benefit. In birds, vigilance is often associated with head‐up postures adopted within a bout of head‐down activity, and this can be used by conspecifics to assess the vigilance of their flock mates. However, vigilance behaviour is not always obvious and other cues ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Guillemain et al . ). Supplemented nestlings also struggled more when handled and emerged faster from tonic immobility.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Guillemain et al . ). Supplemented nestlings also struggled more when handled and emerged faster from tonic immobility.…”
Section: Discussionmentioning
confidence: 97%
“…pale or intense as compared with reference photographs) as one trait of individual appearance that has potential signalling functions (Guillemain et al . ). Additionally, we recorded the owlets' behaviour during handling (i.e.…”
Section: Methodsmentioning
confidence: 97%
“…Intermittent blinking might interfere with such collective detection, which means that foragers might need to allocate more time than expected to antipredator vigilance and rely less on neighbors to detect threats. On the other hand, blinking has been considered to act as a social cue (Curio, 2001) and could even function as a vigilance signal (Guillemain et al, 2012). Whether such social functions are relevant in chickens is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Whether there is an association between pale bird irises and intraspecific gaze sensitivity has not been explicitly studied, but in Great-tailed Grackles Quiscalus mexicanus paler irises can be distinguished relative to the surrounding feathers at greater distances than darker irises (Yorzinski et al 2022). Additionally, Guillemain et al (2012) showed that ducks consistently have different coloured eyelids and irises; these differences may function as signals of vigilance to other members of their flock by indicating whether the eye is open or closed.…”
Section: Social Signallingmentioning
confidence: 99%